Fabrication and characterization of spin-based synaptic devices - Lim, Idayu (Nanyang Technological University, 2023)
Spin orbit torque (SOT) induced chiral domain wall (DW) motion in heavy-metal/ferromagnetic racetrack devices is promising for achieving energy-efficient and high-speed computing elements for edge intelligence[1]. By utilizing fine-grained control of the DW positions and hence, variable resistance readouts, analog synapses can be emulated[2]. This work studies the chiral DW nucleation and dynamics within Pt/Co/MgO wire racetracks, in a parallel multi-wire configuration, to achieve a multi-state variable resistor mimicking synaptic operations. The [ 3/ 0.9 / 1.5] 15 thin film, with Dzyaloshinskii-Moriya interaction of 1.6 mJ/ 2 and effective perpendicular anisotropy of 0.264 MJ/ 3, was fabricated into a multiple racetrack device of varying wire widths (900 nm - 1200 nm). An optimal wire nucleation pad to wire width ratio of 10:1 is selected to ensure preferential nucleation of domains within the nucleation pads. Using the magneto optic Kerr effect microscopy with in situ electrical pulsing set-up, we demonstrate DW motion across the wires in the velocity range of 0.3 – 1.3 m/s, when subjected to injected voltages of 3.5 to 5 V and pulse widths of 0.25 us to 1 us. These results pave the path for engineering chiral spin textures for unconventional computing frameworks.